Influence of coating time on characterization of hydroxyapatite (HAp) coating on WE43 alloy by a chemical solution deposition method - Ngo, Thi Anh Tuyet; Hiromoto, Sachiko; Chi, Linh Do; Pham, Hanh Hong; Pham, San Thy; Thi, Hoa Bui; Giang, Thai Hong (Vietnam Journal of Science and Technology, 2026)
In recent years, biodegradable implants have emerged as an alternative material to avoid long-term complications caused by permanent implants in applications that require a device with a temporary short function, such as endovascular stents and bone repair implants. Mg and some of its alloys are biocompatible materials and have good mechanical properties, which make them become suitable candidates for biodegradable applications. Hydroxyapatite (HAp) has been demonstrated to be an effective coating material to improve corrosion resistance and biocompatibility of the implant materials. In addition, HAp is able to promote bone formation during implantation. In this study, the hydroxyapatite layer (HAp) was formed on the Mg- 4% Y- 3% rare earth alloy (WE43) by a chemical solution deposition method at various coating times from 0,5 hours to 4 hours. The adhesion of HAp layers was evaluated by the pull-off test method. The corrosion resistance of these coatings was measured by polarization tests and Nyquist impedance spectrum performed in a simulated body fluid (SBF) at 37±1oC. XRD analysis demonstrated that HAp coating layers were formed in whole specimens, while the highest intensity of HAp peak was formed at specimens with coating times of 2 and 4 hours. Adhesion test results showed that the coating time of 2 hours-HAp layer had the highest adhesion strength of 6.46 MPa, attributed to the very dense structure and the rod-liked HAp crystal of the outer-coating layer. The corrosion and formation of Mg(OH)2 under the HAp layers were responsible for the decrease in adhesion strength. The polarization tests in SBF at 37±1 oC showed that the corrosion current density decreased with the coating times from 0.5 to 2 hours, and the HAp layer on WE43 was formed on the coating time of 2 hours -specimen improved the corrosion resistance more efficiently than that on other coating times.